Sex specific response in cholesterol level in zebrafish (Danio rerio) after long-term exposure of difenoconazole. (February 2015) - Mu, Xiyan; Wang, Kai; Chai, Tingting; Zhu, Lizhen; Yang, Yang; Zhang, Jie; Pang, Sen; Wang, Chengju; Li, Xuefeng
Abstract: Difenoconazole is a widely used triazole fungicide, its extensive application may potentially cause toxic effects on non-target organisms. To investigate the effect of difenoconazole on cholesterol content and related mechanism, adult zebrafish were exposed to environmental related dosage (0.1, 10 and 500 μg/L) difenoconazole. The body weight and hepatic total cholesterol (TCHO) level was tested at 7, 15 and 30 days post exposure (dpe). The expressions of eight cholesterol synthesis genes and one cholesterol metabolism gene were assessed via Quantitative PCR method. The significant decrease of TCHO level in male zebrafish liver was observed at 15 and 30 dpe, which was accompanied by apparent hepatic cholesterol-genesis genes expression decline. In comparison with males, female zebrafish showed different transcription modification of tested genes, and the cholesterol content maintain normal level during the whole exposure. Graphical abstract: Highlights: Difenoconazle could reduce TCHO level in male zebrafish liver. Difenoconazole could inhibit sterol-genesis genes expression in male zebrafish. Female zebrafish didn't show obvious change of TCHO level after exposure. Difenoconazole could inhibit body weight of both male and female zebrafish. Abstract : Difenoconazle could reduce cholesterol level and sterol-genesis genes expression in male zebrafish. While female zebrafish showed no obvious cholesterol content change during exposure.